Excel as a Sustainable Accounting Solution for SMEs: A Case Study of Bash Coffee Buraydah - Ahmed Mohammed Akrem; Kurniawan Arif Maspul (SEAN Institute, 2024)
This case study looks at the use of Microsoft Excel as a long-term accounting solution for SMEs, using Bash Coffee Buraydah as an example. The study investigates how Excel's familiarity, cost-effectiveness, and customization capabilities contribute to accountants' skills and the company's long-term success. The research gives insights into how Excel improves financial data management, reduces subscription expenses, and improves efficiency and control over accounting operations using a qualitative case study technique that includes interviews and document analysis. The findings inform global SMEs about the benefits of using Excel for cost-effective and long-term accounting processes.